The role of media in the development of eating disorders in adolescents aged of the ripening - Majda, Anna; Braszczyk, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. Eating disorders are a major public health problem in XXI century. Exitus and the young people increase in the world domineered by media, possessory the wide fan of influences, liable to contribute to the height of fallings ill on the anorexia, the bulimia or the stoutness. Aim of the study. The aim of this research was analysis of media influence on eating disorders — anorexia, bulimia and obesity — about adolescents. Materials and methods. This review were conducted with data from 82 adolescent girls and boys with the use of questionnaire, “Beauty- Ugly Scale and measurement of weight and height. To statistical analysis used the Statistica 7.1 program and chi-square test. The significance level was stated as p = 0.05. Results. Underweight were 14.6% adolescents and 11.0% were overweight. Adolescents were dissatisfied of their BMI factor (p = 0.0066). Only 6% bought the advertising products. Most of reviewing adolescent (89%) spent too much time on watching TV and computer, but this fact didn’t correlate with adolescents BMI (p = 0.4036). BMI factor didn’t correlate with perception of information in media (p = 0.7004), but perception of information in media correlated with gender (p = 0.0203). Most of adolescents were agree with stereotype, which is propagate in media (87%), but this fact didn’t correlate with BMI (p = 0.2417). Conclusions. Media play role in etiology of eating disorders by limited physical activity, stimulate to buying unhealthy food, propagate thin cultural ideal of beauty and create and intensified dissatisfaction of body shape. Girls are more exposing to negative impact of media than boys.